Estrabão, Geografia Livro III: Introdução, Tradução do Grego e Notas - Jorge Deserto (DIAITA: Scripta & Realia, 2016)
The third book in Strabo's Geography describes Iberia from the viewpoint of a Greek citizen living in Rome during the rules of Augustus and Tiberius, both Roman emperors in Strabo's lifetime. Having himself witnessed the expansion of the Roman Empire to the western edge of Europe, the geographer from Amaseia highlights the importance attributed to the civilizing and appeasing role exercised by Rome in the westernmost region of the known world. This present edition contains the translation of the Greek text complemented by explanatory footnotes as well as an introduction that includes elements of general interest about the author and his work, a brief outline of the most influential sources in the geographer's writings and the structure of book three of his Geography. In addition the current publication also features an index of geographical terms and another with ancient sources, a map illustrating the contours of the regions referenced by Strabo and a detailed bibliography at the end.